Acceptability of Routine Evaluations Using Patient‐Reported Outcomes of Common Terminology Criteria for Adverse Events and Other Patient‐Reported Symptom Outcome Tools in Cancer Outpatients: Princess Margaret Cancer Centre Experience. (13th August 2019) - Albaba, Hamzeh; Barnes, Tristan A.; Veitch, Zachary; Brown, M. Catherine; Shakik, Sharara; Su, Susie; Naik, Hiten; Wang, Tian; Liang, Mindy; Perez‐Cosio, Andrea; Eng, Lawson; Mittmann, Nicole; et al.
Abstract: Background: Recent studies have demonstrated improved outcomes with real‐time patient‐reported outcome questionnaires (PRO questionnaires) using questions adapted for patient use from the National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE). Outside of the clinical trial setting, limited information exists on factors affecting the completion of PRO questionnaires in routine practice. The primary aim of this prospective cross‐sectional study was to evaluate patient willingness to complete PRO questionnaires on a regular basis and to better understand responder biases to improve patient feedback. Materials and Methods: Patients performing PRO‐CTCAE toxicity and symptom PRO questionnaires in oncology clinics at Princess Margaret Cancer Centre from 2013 to 2016 were assessed for their willingness to complete PRO questionnaires using a nine‐item, tablet‐based acceptability survey. Patient‐reported characteristics (i.e., age, sex, language, marital status, education, occupation, etc.), cancer type, treatment modalities, and health metrics (i.e., Eastern Cooperative Oncology Group) were also collected. Characteristics were evaluated by logistic regression (odds ratios [OR]) using the primary outcome with prespecified levels of significance for univariate ( p ≤ .10), and additional multivariate ( p ≤ .05) testing. Results: A total of 1, 792 patients (median age 60 years; range 18–97) with various cancer diagnoses were assessed. A greater proportion of female (56%) and white (74%) respondents with an annual household income of <$100, 000 (69%) participated. More than half (58%) of respondents were willing to complete PRO questionnaires at every clinic visit, and a high proportion (77%) found utility in reporting physical and emotional feelings to clinicians using PRO questionnaires. In general, patients did not find that PRO questionnaires made clinic visits more difficult (93%). In uni‐ and multivariable testing, patients were more willing to complete sleep‐ and fatigue‐related PRO questionnaires relative to chemotoxicity‐based PRO questionnaires (OR 1.52; p = .012). Patients aged 40–65 versus 18–40 years were also more likely to report high PRO questionnaire acceptability (OR 1.49; p = .025). Additional patient characteristics such as white ethnicity (OR 1.76), Canada as country of birth (OR 1.66), and English language (OR 2.15) relative to other had higher acceptability on uni‐ ( p < .001) and multivariable ( p < .001) analyses. Patients reporting treatment intent as palliative (OR 0.69; p = .0013) or hematological (OR 0.73; p = .027) were less likely to report high PRO questionnaire acceptability on univariable analysis; however, only palliative patients (OR 0.72) maintained this effect on multivariable testing ( p = .012). Patients reporting higher health utility scores (per change in .05) also had significantly increased PRO questionnaire acceptability in uni‐ (OR 1.06; p < .001) and multivariable (OR 1.05; p = .008) analyses. No significant differences in PRO questionnaire acceptability were seen between cancer types, education level, household income, employment status, or treatment modality. Conclusion: Routine assessment using PRO questionnaires is associated with moderate acceptability by patients with cancer. Specific patient characteristics are associated with higher completion willingness. Additional research is necessary to identify factors associated with low acceptability of PRO questionnaires and to develop site‐, ethnicity‐, and treatment‐specific instruments to assess the value of PRO questionnaires for symptom monitoring in clinical practice. Implications for Practice: This study will help to identify the clinical, demographic, and survey characteristics associated with willingness to complete patient‐reported outcome questionnaires regularly in the cancer outpatient setting. Abstract : regorafenib dosing in patients with metastatic or recurrent gastrointestinal stromal tumors after failure of imatinib and sunitinib.